Evaluation and manipulation of tissue and cellular distribution of cardiac progenitor cell-derived extracellular vesicles - Roefs, Marieke T.; Heusermann, Wolf; Brans, Maike A. D.; Snijders Blok, Christian; Lei, Zhiyong; Vader, Pieter; Sluijter, Joost P. G. (Frontiers in Pharmacology, 2022)
Cardiac progenitor cell-derived extracellular vesicles (CPC-EVs) have been successfully applied via different delivery routes for treating post-myocardial infarction injury in several preclinical models. Hence, understanding the in vivo fate of CPC-EVs after systemic or local, i.e. myocardial, delivery is of utmost importance for the further therapeutic application of CPC-EVs in cardiac repair. Here, we studied the tissue- and cell distribution and retention of CPC-EVs after intramyocardial and intravenous injection in mice by employing different EV labeling and imaging techniques. In contrast to progenitor cells, CPC-EVs demonstrated no immediate flush-out from the heart upon intramyocardial injection and displayed limited distribution to other organs over time, as determined by near-infrared imaging in living animals. By employing CUBIC tissue clearing and light-sheet fluorescent microscopy, we observed CPC-EV migration in the interstitial space of the myocardium shortly after EV injection. Moreover, we demonstrated co-localization with cTnI and CD31-positive cells, suggesting their interaction with various cell types present in the heart. On the contrary, after intravenous injection, most EVs accumulated in the liver. To potentiate such a potential systemic cardiac delivery route, targeting the cardiac endothelium could provide openings for directed CPC-EV therapy. We therefore evaluated whether decorating EVs with targeting peptides (TPs) RGD-4C or CRPPR connected to Lamp2b could enhance EV delivery to endothelial cells. Expression of both TPs enhanced CPC-EV uptake under in vitro continuous flow, but did not affect uptake under static cell culture conditions. Together, these data demonstrate that the route of administration influences CPC-EV biodistribution pattern and suggest that specific TPs could be used to target CPC-EVs to the cardiac endothelium. These insights might lead to a better application of CPC-EV therapeutics in the heart.